The Internationalization of Psychology Journals in Brazil: A Bibliometric Examination Based on Four Indices - Chris Fradkin (Paidéia (Ribeirão Preto))
Abstract: There is considerable variability among psychology journals in Brazil, in terms of presence on the international stage. However, research as to why is very scarce. This study empirically examined the relationship between several indices of internationalization and real-world internationalization, among these journals. 661 articles from the top-17 psychology journals in Brazil were coded for: English-language text, editorial board makeup, lead author institution, and article type. Analyses revealed that successful internationalization was associated with: (i) lead author institution from a native English-speaking country; (ii) empirical articles; and (iii) editorial board members from a native English-speaking country. Use of English-language text was not associated with successful internationalization. These findings suggest that the path to internationalization for psychology journals in Brazil may depend on increased publishing of findings from English-speaking countries; or at the very least: increased collaboration between Brazilian and native English-speaking scholars.